Using ICON Satellite Data to Forecast Equatorial Ionospheric Instability Throughout 2022 - D. L. Hysell; A. Kirchman; B. J. Harding; R. A. Heelis; S. L. England; H. U. Frey; S. B. Mende (Space Weather)
Abstract Numerical forecasts of plasma convective instability in the postsunset equatorial ionosphere are made based on data from the Ionospheric Connections Explorer satellite (ICON) following the method outlined in a previous study. Data are selected from pairs of successive orbits. Data from the first orbit in the pair are used to initialize and force a numerical forecast simulation, and data from the second orbit are used to validate the results 104 min later. Data from the IVM plasma density and drifts instrument and the MIGHTI red‐line thermospheric winds instrument are used to force the forecast model. Thirteen (16) data set pairs from August (October), 2022, are considered. Forecasts produced one false negative in August and another false negative in October. Possible causes of forecast discrepancies are evaluated including the failure to initialize the numerical simulations with electron density profiles measured concurrently. Volume emission 135.6‐nm OI profiles from the Far Ultraviolet (FUV) instrument on ICON are considered in the evaluation.